Islam dan Filsafat Ilmu - Hazarul Aswat (Adabuna)
Islam is the source of all sources of knowledge that depart from the "premise of faith", or based on thoughts of faith and belief that rely on the Koran revealed by Allah Subhanahu Wa Ta'ala and the Hadith of Rasulullah Muhammad Shallallahu'Alaihi Wasallam to distinguish between rights and falsehood and be a clarification and guidance for His people. Knowledge obtained by humans or animals later from science or what is called the philosophy of science. Where did the knowledge come from or through what knowledge was obtained, that is the question of how toriqokh or how to get the knowledge or where did the knowledge obtained by mankind come from. The knowledge possessed by mankind on the face of this earth, all originate from one source, namely Allah Subhanahu Wa Ta'ala through the holy words of the Prophet Muhammad Shallallahu'Alaihi Wasallam and there is not the slightest source of knowledge that escapes His knowledge. Allah Subhanahu Wa Ta'ala. Only a different way or toriqoh that He gave to mankind.